84.6k views
2 votes
Solve the equation shown for x.
-4(2x+9)+3x=6-4(x-3)
STEP BY STEP EXPLANATIONN

User Expz
by
4.3k points

2 Answers

6 votes

Answer:

x = -54

Explanation:

6 - 4(x - 3) = 6 - 4x + 12 (4 times x, 4 times -3) = -4x + 18 (12 + 6).

-4(2x + 9) + 3x = -8x (-4 x 2x) - 36 (-4 x 9) + 3x = -5x (-8x + 3x) - 36.

-5x - 36 = -4 + 18

+36 +36

-5x (-36 + 36 = 0) = -4x + 54 (18 + 36)

+4x +4x

-x = 54 (-4x + 4x = 0)

÷1 ÷1

x = -54

User Harald Brinkhof
by
4.7k points
6 votes

Answer:

x= -54

Explanation:

distribution- -8x-36+3x=6-4x+12

add like terms- -5x-36=-4x+18

get x alone -5x=-4x+54. added 36 to both sides

add 4x to both sides -x=54

divide by -1. x= -54

User Dreinoso
by
4.7k points